2019
DOI: 10.1177/0363546519854101
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Additional Anterolateral Structure Augmentation to Controlling Pivot Shift in Anterior Cruciate Ligament Reconstruction

Abstract: Background: Several types of anterolateral structure (ALS) augmentation procedures in anterior cruciate ligament (ACL) reconstruction have been reported. However, information is limited regarding the effect of additional ALS augmentation on rotatory stability in a clinical setting. Purpose/Hypothesis: This study aimed to investigate the contribution of additional ALS augmentation in ACL reconstruction in cases with a high risk of residual pivot shift. The 2 hypotheses were as follows. First, additional ALS aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 68 publications
1
28
0
1
Order By: Relevance
“…The results of the present study can contribute to the evaluation of the optimal indications for additional procedures to ACLR (eg, anterolateral ligament reconstruction, 28 , 29 anterolateral tenodesis, 8 , 33 and anterolateral structure augmentation 30 ), and greater preoperative instability on pivot-shift testing may be a factor. Furthermore, it may be desirable to use the cutoff value calculated by quantitative measurements as per this study because these quantitative values enable surgeons to evaluate indications more objectively.…”
Section: Discussionmentioning
confidence: 85%
“…The results of the present study can contribute to the evaluation of the optimal indications for additional procedures to ACLR (eg, anterolateral ligament reconstruction, 28 , 29 anterolateral tenodesis, 8 , 33 and anterolateral structure augmentation 30 ), and greater preoperative instability on pivot-shift testing may be a factor. Furthermore, it may be desirable to use the cutoff value calculated by quantitative measurements as per this study because these quantitative values enable surgeons to evaluate indications more objectively.…”
Section: Discussionmentioning
confidence: 85%
“…Ferretti et al [15] reported that the incidence of ALL injuries associated with ACL tears is about 90%. For these reasons, several clinical studies of combined ACLR and ALLR have been performed and have reported improved rotatory stability of the knee [27,29,42,43,48]. Studies have shown that the pivot-shift test is a reliable examination in evaluating functional instability [4,25].…”
Section: Discussionmentioning
confidence: 99%
“…After the associated fracture had been xed, the pivot-shift test was performed by the senior attending surgeon prior to xing the ALL tibial avulsion fracture [27,28,48,43]. The patients were routinely followed up at 1, 3, 6, 12, and 24 months postoperatively.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…There has been a renewed worldwide interest in defining the anterolateral corner of the knee following the publication of the precise anatomic details of the anterolateral ligament (ALL) [7][8][9]. Cadaveric as well as clinical studies have reported on the benefits of supplementing ALL reconstruction with ACL reconstruction in cases with concomitant injuries [10][11][12]. However, there are studies that claim that ALL reconstruction may be detrimental to knee function and produce early joint degeneration and lateral extra-articular reinforcement may be the preferred reconstruction option [13,14].…”
Section: Introductionmentioning
confidence: 99%